Management of Refractory Status Epilepticus: An International Cohort Study (MORSE CODe) Analysis of Patients Managed in the ICU. (13th September 2022) - Chiu, Wei-Ting; Campozano, Vanessa; Schiefecker, Alois; Rodriguez, Dannys Rivero; Ferreira, Daniel; Headlee, Amy; Zeidan, Sinead; Grinea, Alexandra; Huang, Yao-Hsien; Doyle, Kevin; Shen, Qi; Gómez, Diana; et al.
Abstract : Background and Objectives: Status epilepticus that continues after the initial benzodiazepine and a second anticonvulsant medication is known as refractory status epilepticus (RSE). Management is highly variable because adequately powered clinical trials are missing. We aimed to determine whether propofol and midazolam were equally effective in controlling RSE in the intensive care unit, focusing on management in resource-limited settings. Methods: Patients with RSE treated with midazolam or propofol between January 2015 and December 2018 were retrospectively identified among 9 centers across 4 continents from upper–middle-income economies in Latin America and high-income economies in North America, Europe, and Asia. Demographics, Status Epilepticus Severity Score, etiology, treatment details, and discharge modified Rankin Scale (mRS) were collected. The primary outcome measure was good functional outcome defined as a mRS score of 0–2 at hospital discharge. Results: Three hundred eighty-seven episodes of RSE (386 patients) were included, with 162 (42%) from upper–middle-income and 225 (58%) from high-income economies. Three hundred six (79%) had acute and 79 (21%) remote etiologies. Initial RSE management included midazolam in 266 (69%) and propofol in 121 episodes (31%). Seventy episodes (26%) that were initially treated with midazolam and 42 (35%) with propofol required the addition of a second anesthetic to treat RSE. Baseline characteristics and outcomes of patients treated with midazolam or propofol were similar. Breakthrough (odds ratio [OR] 1.6, 95% CI 1.3–2.0) and withdrawal seizures (OR 2.0, 95% CI 1.7–2.5) were associated with an increased number of days requiring continuous intravenous anticonvulsant medications (cIV-ACMs). Prolonged EEG monitoring was associated with fewer days of cIV-ACMs (1–24 hours OR 0.5, 95% CI 0.2–0.9, and >24 hours OR 0.7, 95% CI 0.5–1.0; reference EEG <1 hour). This association was seen in both, high-income and upper–middle-income economies, but was particularly prominent in high-income countries. One hundred ten patients (28%) were dead, and 80 (21%) had good functional outcomes at hospital discharge. Discussion: Outcomes of patients with RSE managed in the intensive care unit with propofol or midazolam infusions are comparable. Prolonged EEG monitoring may allow physicians to decrease the duration of anesthetic infusions safely, but this will depend on the implementation of RSE management protocols. Goal-directed management approaches including EEG targets may hold promise for patients with RSE. Classification of Evidence: This study provides Class III data that propofol and midazolam are equivalently efficacious for RSE.